1993
DOI: 10.1103/physrevlett.70.746
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the total ionization cross section and spin asymmetry in electron-hydrogen scattering from threshold to 500 eV

Abstract: We present the total ionization cross section and spin asymmetry at projectile energies ranging from threshold to 500 eV for electron-impact excitation of atomic hydrogen. They are calculated using the convergent close-coupling formalism of Bray and Stelbovics [Phys. Rev. A 46, 6995 (1992)]. Both observables are found to be in complete quantitative agreement with measurements over almost the entire energy range. This is the only electron-atom scattering theory that is able to achieve this result to date. [13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
85
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(99 citation statements)
references
References 23 publications
14
85
0
Order By: Relevance
“…This model accurately describes the physics of the scattering whenever the positronium-formation cross section is negligible, in particular, above 100 eV for this system. The total ionization cross section results in this energy region are in excellent agreement with the recent measurements of Jones et [2], and the quantitative agreement with the Poet-Temkin model e -H problem that treats states with only zero orbital angular momentum [3]. The latter work demonstrated the important result that pseudoresonances, typically associated with square-integrable expansions of the continuum, diminish and disappear with increasing basis size.…”
supporting
confidence: 85%
“…This model accurately describes the physics of the scattering whenever the positronium-formation cross section is negligible, in particular, above 100 eV for this system. The total ionization cross section results in this energy region are in excellent agreement with the recent measurements of Jones et [2], and the quantitative agreement with the Poet-Temkin model e -H problem that treats states with only zero orbital angular momentum [3]. The latter work demonstrated the important result that pseudoresonances, typically associated with square-integrable expansions of the continuum, diminish and disappear with increasing basis size.…”
supporting
confidence: 85%
“…Bray and Stelbovics [14] showed that the positive-energy pseudostates included in their CCC calculations could be used to evaluate ionization cross sections, and obtained the first e-H total ionization cross section (TICS) results that were in complete agreement with experiment over a wide range of energies. In addition to CCC and IERM, other state-of-the-art methods include, for example, R-matrix with pseudostates (RMPS) [15], hyperspherical close-coupling (HSCC) [16] and time-dependent close-coupling (TDCC) [17].…”
Section: Introductionsupporting
confidence: 49%
“…In particular, one of the leading theories for e-H and e-He scattering processes, the CCC theory, is shown to provide accurate angular distributions but incorrect absolute TDCS results (i.e., lower by factors of 2-7) in the energy region from threshold to 25 eV above. This is particularly remarkable given that the CCC theory predicts correct absolute total ionization cross sections [10]. In contrast, the simpler DPW approach, which we have restricted to the u 12 p geometry owing to the screening approximation it employs, gives reasonably accurate predictions of both the angular distribution and the absolute TDCS's over the entire energy region considered here.…”
Section: Fig 2 Equal Energy Sharing E-h Triply Differential Cross Smentioning
confidence: 80%
“…The implicit implication was that accurate accounting of target effects on the various electronic partial waves as well as treatment of electronelectron interactions are necessary to obtain agreement with absolute data and that omission of these effects can lead to disagreement with experiment by factors of 2-200 [9]. In response to these first absolute measurements for He, theorists have since devoted increased attention to providing not only accurate angular distributions but also accurate absolute cross sections [8,[10][11][12]. Absolute measurements near threshold are also necessary to determine the threshold law for fragmentation of three-body Coulomb systems.…”
mentioning
confidence: 99%